The lady and the peacock the life of Aung San Suu Kyi - Popham, Peter (Experiment, 2012)
Nobel Peace Prize Laureate Aung San Suu Kyi known to the world as an icon for democracy and nonviolent dissent in oppressed Burma, and to her followers as simply "The Lady" has recently returned to international headlines. Now, this major new biography offers essential reading at a moment when Burma, after decades of stagnation, is once again in flux. Suu Kyi's remarkable life begins with that of her father, Aung San. The architect of Burma's independence, he was assassinated when she was only two. Suu Kyi grew up in India (where her mother served as ambassador), studied at Oxford, and worked for three years at the UN in New York. In 1972, she married Michael Aris, a British scholar. They had two sons, and for several years she lived as a self-described "housewife" but she never forgot that she was the daughter of Burma's national hero.